Changes to the House of Commons Legislation Procedure during the 1997 and 2005 Parliaments - Michalak, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2009)
The Select Committee on Modernisation of the House of Commons was established in June 1997 with a remit to “consider how the practices and procedures of the House should be modernised”. During the 1997 and 2005 it has put forward a number of proposals for reform, many of which have subsequently been adopted by the House. This article explains the background to the establishment of the Committee and the Modernisation Programme. It also explains the nature of the Modernisation Committee (which is unusual in that it has been chaired by the Leader of the House) and outline the key changes to the legislation procedures of the House of Commons during the 1997 and 2005 Parliaments (Pre-legislative Scrutiny, Timetabling of legislation, Carry Over of Bills). Furthermore this paper looks at the future of the Modernisation Committee and the prospects for further reform of the House of Commons practices and procedures.